The Hidden Side of Regional Economic Growth in Bali - Trisanthi, Nyoman Rahayu; Saskara, Ida Ayu Nyoman (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This research's novelty lies in its examination of the development of a multidimensional, non-compensatory framework, based on the Adjusted Mazziotta–Pareto Index (AMPI), which integrates regional fiscal priorities and socio-economic outcomes to map patterns of economic growth performance. Research Objectives: This research aims to assess the patterns and dynamics of economic growth performance across regencies and municipalities in Bali Province before, during, and after the COVID-19 pandemic, with particular attention to differences in growth quality, resilience, and recovery. Research Methods: This research employs the Adjusted Mazziotta–Pareto Index (AMPI) analysis from 2016 to 2024, which is constructed using five indicators: government spending on public services, education, health, lowering the poverty rate, and supporting GRDP growth. Empirical Results: The results indicate that economic growth performance across regencies and municipalities in Bali Province is dynamic and heterogeneous, varying by region and period. Implications: Regional development policies should prioritize the quality and resilience of economic growth by balancing public spending across structurally impactful sectors and adopting adaptive fiscal strategies. JEL Classification: H72, O47, R11, I32